Ceftriaxone-and-cefixime-resistant Neisseria gonorrhoeae in a 26-year-old-male with gonococcal urethritis: a case report - Prameshwara, Almarissa Ajeng; Prawarni, Vidyadhari Puspa; Susetiati, Devi Artami; Nuryastuti, Titik (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2024)
Introduction: Gonorrhoea is the most prevalent sexually transmitted infection (STI) in Indonesia. The increasing resistance of Neisseria gonorrhoeae to antibiotics has prompted the World Health Organization (WHO) to classify gonorrhoea as an urgent public health threat. Reports of resistance to third generation extended-spectrum cephalosporins (ESCs), such as cefixime and ceftriaxone, against N. gonorrhoeae are rare in Indonesia. This study aims to present a case of cefixime and ceftriaxone resistance in a 26-year-old man with gonococcal urethritis. Case Description: A 26-year-old man presented to an STI clinic with a two-week history of increased urethral discharge. He reported a history of sexual activity with multiple partners. Physical examination revealed mucopurulent exudate and thick greenish-white pus from the external genitalia. Microscopic examination of a urethral smear identified numerous polymorphonuclear cells (>10 PMN/high-power field) and Gram-negative intracellular diplococci. Bacterial culture confirmed the presence of Gram-negative diplococci consistent with N. gonorrhoeae. Polymerase chain reaction (PCR) testing further confirmed N. gonorrhoeae. Susceptibility testing revealed resistance to both cefixime and ceftriaxone. The patient was treated with dual therapy, consisting of a single oral dose of azithromycin (1 g) and cefixime (400 mg). Complete symptom resolution was achieved within one week. Conclusion: Third-generation ESCs, including injectable ceftriaxone and orally administered cefixime, are the most commonly used antibiotics for gonorrhoea treatment. Resistance to these drugs represents a significant global health threat. Discrepancies between antibiotic susceptibility test results and clinical outcomes highlight the need for further investigation into underlying factors contributing to treatment efficacy.